TACI expression is associated with a mature bone marrow plasma cell signature and C-MAF overexpression in human myeloma cell lines - Moreaux, Jérôme; Hose, Dirk; Jourdan, Michel; Reme, Thierry; Hundemer, Michael; Moos, Marion; Robert, Nicolas; Moine, Philippe; Vos, John De; Goldschmidt, Hartmut; Klein, Bernard (Haematologica, the hematology journal, 2007)
Background and Objectives BAFF and APRIL stimulate the growth of multiple myeloma (MM) cells. BAFF and APRIL share two receptors - TACI and BCMA - and BAFF binds to a third receptor, BAFF-R. We previously reported that TACI gene expression is bimodal in 18 human MM cell lines (HMCL), being either present or absent, unlike BCMA that is expressed on all HMCL. BAFF-R is lacking. TACI expression is a good indicator of a BAFF-binding receptor in HMCL. In primary MM cells, the level of TACI expression correlates with a characteristic phenotypic pattern: TACIhigh MM cells resemble bone marrow plasma cells and TACIlow resemble plasmablasts. The aim of this study was to further characterize the role of TACI expression in MMDesign and Methods Using gene expression profiling, we investigated whether these patterns are kept in TACI+ or TACI− HMCL.Results Eighty genes/EST interrogated by Affymetrix microarrays were differentially expressed between TACI+ and TACI− HMCL, particularly c-maf, cyclin D2, and integrin β7. Triggered by the finding that TACI and c-maf expressions correlate in TACI+ HMCL, we demonstrated that TACI activation influences c-maf expression: (i) activation of TACI by BAFF or APRIL increases c-maf, cyclin D2, and integrin β7 gene expressions in TACI+ HMCL, (ii) blocking of autocrine BAFF/APRIL stimulation in some TACI+ HMCL by the TACI-Fc fusion protein reduces c-maf, cyclin D2, and integrin β7 gene expression, (iii) nucleofection of siRNA to c-maf decreases c-maf mRNA levels and reduces the expression of cyclin D2 and integrin β7 gene expressions, without affecting TACI expressionInterpretation and Conclusions We conclude that TACI activation can upregulate c-maf expression which, in turn, controls cyclin D2, and integrin β7 gene expression.
Gesehen am 28.01.2022